Sulla rotta di Taprobane: nuove allusioni geograﬁche nelle Storie vere - Braccini, Tommaso (Hyperboreus, 2024)
Lucian of Samosata, within his works, demonstrates in more than one instance some attention to the routes between the Roman empire and India, and the localities that had come to prominence in his day, starting with the port of Muziris, of which he conveys one of the earliest records and the only one in a non-technical text. In many other respects (ship-swallowing whales in primis), Lucian seems indebted to the coeval literature on Taprobane. Particularly within the True Histories, various hitherto neglected parodic references to the travel literature circulating in his day seem to emerge, which can be recovered only in skeletal form from mentions by Ptolemy, Pliny, and later accounts of Arab and Oriental origin. Just to mention a few instances, the island of the Onoskeleai, whether Kobalousa, Kabalousa, or Ekbalousa, seems to refer in its name to the Barousai/Balus/Langabalus islands inhabited by cannibals; the forest of trees ﬂoating in the sea seems to recall the “sea trees” mentioned by Pliny; the prodigious footprints of Heracles and Dionysus may allude to traditions on the Sri Pada, the sacred imprint of a deity on a mountain of Sri Lanka/Taprobane, already attested in antiquity and perhaps also featured by Ptolemy. While not denying the importance of parodic references to the “classics”, primarily the Odyssey, this line of inquiry sheds light on another aspect of Lucian’s parodic mixis.